Evaluation of Musculoskeletal Loads and Pain in Physical Therapists Treating Neurological Patients - Lee, Daehee; Jeon, Hyejoo (Universitas Airlangga, 2024)
Introduction: Work-related musculoskeletal disorders (WRMDs) are one of the major health problems among physical therapists treating neurological patients. Therefore, this study aimed to determine the risk factors for developing WRMDs in physical therapists in South Korea treating neurological patients. Methods: This research is an analytical observational study with a cross-sectional design. In this study, 30 physical therapists who treat neurological patients were recruited by randomly selecting respondents to flyers posted throughout the hospital. To evaluate risk levels, during the transfer of the patient from the wheelchair to the treatment table and during treatment, the Rapid Entire Body Assessment (REBA) was performed. Moreover, physical therapists were assessed for musculoskeletal symptoms through the Nordic Musculoskeletal Questionnaire (NMQ) survey. Results: The findings revealed that during the treatment session, the REBA score was 43.33% for medium and high risk level and 13.33% for very high risk level. Meanwhile, during the transfer session, the REBA score was 40% for high risk level and 60% for very high risk level. The results of the Nordic musculoskeletal questionnaire showed that physical therapists felt significant pain in the wrist/hand, shoulders, neck, lower back, and knee. Conclusion: Physical therapists treating neurological patients have a high risk of developing WRMDs. Thus, changes need to be made regarding the working pattern of physical therapists, and more detailed evaluations of ergonomic risk factors are required.